Between metrics and narratives: definition and applications of Narrative Bibliometrics - Torres-Salinas, Daniel (Anuario ThinkEPI, 2023)
Narrative Bibliometrics has emerged as a novel evaluation tool in the academic arena, particularly in response to new evaluation criteria laid out by CoARA and other regulatory frameworks. This approach incorporates bibliometric indicators into an explanatory narrative to defend and contextualize researchers’ scientific curricula. The narrative allows for the detailing of the merits, attention, dissemination, and influence of scientific contributions, avoiding simple quantification (bean counting). Narrative Bibliometrics falls under Evaluative Bibliometrics, aiming to serve as a useful tool for evaluators in decision-making. The proposal also explores different applications of bibliometric narratives, such as position, context, agents, and audience narratives, providing concrete examples and emphasizing the need for multidimensional contextualization and verifiability.
Keywords: Narrative Bibliometrics; CoARA; Evaluative Bibliometrics; Narrative curriculum; Bibliometric indicators; Contextualization